2000
DOI: 10.1007/bf03218204
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic ciardiac rupture with acute ascites

Abstract: A rare accumulation of serous ascites following traumatic cardiac rupture is reported for a 21-year-old man transferred to the emergency center of our hospital from a community hospital suffering from severe shock due to a motorcycle accident. Computed tomography scan showed moderate pericardial and intrapelvic fluid accumulation strongly suggesting cardiac and visceral injuries. An emergency sternotomy disclosed a rupture of the right atrial appendage, successfully closed with primary sutures. A laparotomy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The mechanism of injury is thought to be compression of the chest cage that crushes the heart between the sternum and the vertebras dorsales or via direct transmission of a momentary increase in intrathoracic pressure to the heart chambers [4]. Several reports have noted that serous ascites following cardiac rupture due to blunt chest trauma is an incipient symptom [5,6]. Ascites resulting from mechanical impedance to the hepatic venous outflow has been documented in detail.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism of injury is thought to be compression of the chest cage that crushes the heart between the sternum and the vertebras dorsales or via direct transmission of a momentary increase in intrathoracic pressure to the heart chambers [4]. Several reports have noted that serous ascites following cardiac rupture due to blunt chest trauma is an incipient symptom [5,6]. Ascites resulting from mechanical impedance to the hepatic venous outflow has been documented in detail.…”
Section: Discussionmentioning
confidence: 98%
“…Koyama et al reported a case of traumatic cardiac rupture with acute ascites (Koyama et al 2000). In that article, an emergency sternotomy revealed a rupture of the right atrial appendage.…”
Section: Discussionmentioning
confidence: 99%